Myanmar : Technical Assistance Report-External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Assistance Report paper highlights that the work on verifying reasonable size of coverage adjustments for Myanmar's imports was addressed during the mission, using bilateral trade data from Thailand and China. The mission illustrated how granular data can be used to help determine proper adjustments to improve the coverage of the International merchandise trade statistics, using Thailand's data on exports to Myanmar cross-classified by border checkpoint and 2-digit HS code. The data indicated potential under-coverage of Myanmar imports for a few checkpoints sharing land border with Thailand. Although the actual travel expenditure per person per day for certain years is likely to be lower than the time series published by the Ministry of Hotels and Tourism given continuous depreciation of Kyat over the past five years, this factor should unlikely outweigh the effect of growing numbers of inbound tourists. Balance-of-payments compilation file used by the Central Bank of Myanmar Balance of Payments Section has now been modified to accommodate suggested coverage adjustments for imports, and the new estimation model for freight and insurance on imports proposed during March 2019 mission.